Preparation and Evaluation of High Nutrition Value Crackers Enriched With Some Leafy Vegetables - Wafaa, K. Galal; Wafaa, Z. Elfeky; Eman, S. Mohamed (Food Technology Research Journal, 2023)
The present study is carried out to evaluate the nutritional, functional, and sensorial properties of crackers enriched with green leafy vegetables powder (GLVP) namely (chicory, dill, coriander, parsley, and rocket) at 5, 10 and 15 % replacement of dried leaves/100 g wheat flour. Crackers were found to be nutritionally rich in protein, fiber, minerals and antioxidant activity compared with control crackers. Sensory properties of crackers showed that up to 10% wheat flour replacement of green leaves powder were acceptable. Results showed that the highest content of protein observed in crackers with 10% parsley, the highest content of ash was in crackers with 10% dill and the highest content of crude fiber and fat content in crackers with 10% chicory compared with control. There was a significant increment in the antioxidant activity with the addition of green leaves powder. The highest content of antioxidant activity and total phenolic content of prepared crackers with dill (38.64% -83.06 mg /100g) respectively, but the highest content of total Flavonoids in crackers with 10% chicory (67.5 mg /100gm). The highest content of chlorophyll a was in the crackers with 10% rocket and the lowest content in the crackers with 10% dill but the highest content of chlorophyll b was in the crackers with 10% coriander and the lowest was in crackers with 10% dill on the other hand the highest carotenoids was in the crackers with 10% coriander but the lowest was in crackers with 10% dill.